Forced migration and indigenous knowledge of displaced Emberá and Uitoto populations in Colombia: An ethnobotanical perspective - Victor Hugo Gonzalez Betancourt; Patricio Ortiz; Gina Frausin (Mundo Amazónico, 2012)
<!--[if gte mso 9]> <![endif]--> Relatively little attention has been given to documenting changes in the ethnobotanical knowledge of displaced indigenous groups in Colombia. Such information is highly valuable because it contributes to our understanding of the changes that occur during this process of displacement, cultural transformation and loss, and because it eventually could shed some light in designing social, economic, and educational policies that would facilitate their incorporation into main stream culture, through ways that validate their indigenous identity, knowledge, and traditions. Based on our on-going research, herein we summarize ethnobotanical information of two indigenous groups currently residing in the city of Florencia (capital of the Department of Caquetá) in the Northwestern Amazon basin: the Emberá, originally from northwestern Colombia, and Uitoto, originally from the Colombian Amazon. By focusing in the indigenous ethnobotanical knowledge of these two displaced groups, we intend to show the revitalization of ethnobotanical knowledge, resilience, and multiple resources in form of ancestral knowledge that are brought and transmitted by these groups as they struggle for survival, in many times hostile urban environments. We hope to draw more attention to and encourage similar studies on other displaced indigenous populations in Colombia as well as in other areas of Latin America. <!--[if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->